Analysis and Research on the "last mile" distribution innovation model of e-commerce express delivery. Issue 4 (March 2019) - Zhang, Yu; Fan, Xiani; Zhou, Li
Abstract: With the rapid development of e-commerce, the number of online shopping transactions has increased year by year. Selecting products online, paying online, and waiting for packages to be delivered to the door has become a part of life shopping for many people, from online orders to offline delivery. Its intermediate process needs to be completed with the help of the logistics company to realize the circulation of goods. The final distribution phase of e-commerce logistics, that is, the "last mile" delivery of e-commerce express, this process will directly target the final customer. This stage has become a key stage affecting the quality of logistics and service and customer satisfaction.